Borders of Humor: Is There a Hometown of Laughter? - Bas, Bayram; Aslan, Emine Ulu (GELENEKSEL YAYINCILIK LTD STL, 2020)
The human of 21st century, although the situation they laugh change over time, maintain a sense of humor that develops both collectively and individually, as their ancestors did. This phenomenon, which we divide into many genres such as irony, wit, mockery, satire, parody, grotesque, etc. but generally called as humor and concludes with a laugh situation, is based on reasons such as superiority, relaxation and incompatibility by humor theorists. The laugh forms created by this humorous situation have been depicted as aristocratic, folk, cynical, cheerful, carnival, natural and artificial smile by thinkers since ancient times. Regardless of its cause and effect, although the mental and emotional foundations are universal components, the work of humor built on these foundations maintains its originality and variability for every nation. Because the hero of humor is human and basically reflects a social phenomenon. Humor, since it is created by filtering the contexts such as culture, memory, cognition and language, needs to be examined by taking into account these variables. Because these contexts guide the marketing and advertisement strategies of the countries, the world of cinema and television, education, literature and other broadcasting life, even politics and the usage of the humor element in these areas. The effect that humor wants to create and expects from its interlocutor can only be achieved through the discovery of the codes that these contexts refer to. The humor that we can analyze thanks to these codes, which we can process to the extent that cultural and linguistic contexts offer us, has a serious theoretical structure in the background, although it seems close to the comic one. In this study, a detailed theoretical framework on humor and laughter is aimed and the bases of differences in countries' sense of humor are emphasized. These differences have been tried to be conveyed through cultural, memory-based, linguistic and cognitive contexts, and supported by examples from both countries' humorous understanding and structures supporting this understanding. As a conclusion, it is seen that the importance of humor and its components changed from culture to culture because the reasons of the need of each society to create humor are different. Humor is universal because it needs to be present in every society as a social phenomenon and requires some cognitive processes in the human mind to complete its formation. It is also local because societies have different cultural and linguistic codes and therefore do not share the same humor. Even in the case of an individual form of laughter, the humorous situation is a communicative metaphor based on responding to a person, situation or text, and has assumed the task of supporting social life by meeting the expectations of individuals. In addition, it is concluded that the collective and individual processes of humor feed each other and need each other to grasp constitution of humor.
Keywords: Laughter; humor; culture; memory; cognition; Arts & Humanities - Other Topics